A PECULIAR NATURAL WONDERLAND OF SOUTH CHINA SEA: A BIRD’S EYE VIEW - Azra, Mohamad Nor; Noor, Mohd Iqbal Mohd; Seman, Juneta-nor Abu; Seong Wei, Lee, Dr (UI Scholars Hub, 2023)
The South China Sea research agenda has increased over the years. However, no scientometric studies have been performed on this topic, which has helped analyze the research on the South China Sea throughout many years. Thus, this study aimed to investigate the global findings of previous research on the South China Sea, development trends, and trending issues surrounding the sea. Literature was extracted from the Web of Science Core Collection (WOSCC) database, and the CiteSpace software was used to visualize the data analyzed. The survey included 12,755 articles. Overall, the number of publications increased annually. Acta Oceanologica Sinica and the Chinese Academy of Science are the journals and affiliations with the most relevant studies, respectively. China is at the forefront of research regarding the South China Sea, with more than four times as many articles as the USA. The most common keywords were variability, ocean, model, evolution, circulation, and water. The most recent keywords were East Asian monsoon and metabolite, indicating a shift in research priorities. This study is the first to perform a scientometric analysis of the South China Sea. This study is expected to assist researchers, academics, and investigators in exploring potential research directions in the South China Sea. The study also hopes to contribute towards Sustainable Development Goals 11 and 14, Sustainable Cities and Communities, and Life Below Water.